Resource sharing and networking among the libraries of the Ministry of Human Settlements and attached agencies - Lucas, Zenaida F. (1986)
This study looked into the resources and state of resource sharing with implications for networking among the libraries of the Ministry of Human Settlements and 17 attached agencies. It describes their information resources, services, budget, equipment, manpower and clientele as well as their attitudes toward the establishment of a human settlements information network.